Integrated Ethnomedicine Study in Silico of Medicinal Plants for Hypertension - Lestariningrum, Wahyu Titis; Kintoko, Kintoko; Farid , Muhammad (Journal La Lifesci, 2024)
This study aims to discover a new formula from natural ingredients that are effective as antihypertensive agents through ethnomedicine research and in silico testing. The study was conducted at the Beringharjo Jamu Market in Yogyakarta by identifying the three most commonly used plants by vendors: Sambiloto (Andrographis paniculata), Akar Pule Pandak (Rauvolfia serpentina), and Seledri (Apium graveolens). Ethnomedicine studies used quantitative parameters such as Relative Frequency of Citation (RFC), Use Value (UV), Fidelity Level (FL), and Informant Consensus Factor (ICF). Subsequently, in silico tests were conducted with a network pharmacology and molecular docking approach to analyze protein-target interactions and test the potential of active compounds from these three plants. The results showed that Sambiloto had the best affinity through the compound Andrographolide with an affinity value of -561 kcal/mol. This study confirms that the three plants have the potential to contain key active ingredients for hypertension therapy using the Ethnomedicine Driven Reversal Approach System (EDRAS), which has proven to be effective and efficient.